The study of water losses using knowledge based system approach - Kabbashi, Nassereldeen Ahmed; Hasif, Mohd. A.; Mirghani, Mohamed Elwathig Saeed (Capital Publishing Company, 2017)
Water represents about 70 % of the whole earth surface yet it is limited in its availability as a freshwater to human benefits. The importance is on freshwater assets since it is freshwater resources that are used for daily usage, agricultural and industrial intentions. According to Hu (2006), freshwater represents about 2.76 % of the total water available on earth. And even with this, it is only less than 1 % which is readily available to be accessed and used by human. About 20 % of the world’s population lack access to safe drinking water and about eighty countries, which inhabitat 40 % of the world’s population are in severe water crisis situation. Non-revenue water (NRW) can be defined as the amount or quantity of lost water starting from the water treatment plant to the consumers. In other words, it occurs within the distribution systems added with amount of water that is authorized to use but not billed.